Mining design and short-term production scheduling by using 3D modeler in Coal mining at PT. Internasional Prima Coal, Palaran District, Samarinda City, East Kalimantan Province - Berhitu, Theo; Fanani, Yazid; Cahyono, Yudho Dwi Galih (Journal of Earth and Marine Technology (JEMT), 2022)
PT. International Prima Coal is a subsidiary of a combination of two companies, namely PT. Bukit Asam (Persero) Tbk and PT. Mega Raya Kusuma which is engaged in coal mining in East Kalimantan, with an area of 3,238 hectares of Mining Business Permit in Bantuas and Handil Bakti Villages, Palaran District, Samarinda City which is planning to open a new block, namely North Eagle 3 block for the sustainability of coal production. This is the background for the author to research mining design and production schedule. This study aims to analyze resources and reserves, design mining, determine the combination of tools and monthly production scheduling. The research method used is qualitative and quantitative methods. the quantitative method will produce data such as the value of resources and reserves, slope geometry, SR (Stripping Ratio), and the amount of production per month. The qualitative method will produce data such as haul road designs, mining methods, mining sequences. Based on the results of modeling of coal deposits in the northern pit eagle 3 has 3 seams (Q050, Q070, Q080) with a total measured resource calculated by the polygon method is 726,898 tons. The design of the mining pit limit at an elevation of 0 masl is the contour of the Q070 seam structure with a total coal reserve of 66,516 tons and OB 651,952 bcm with SR 10. The haul road is made of 2 lanes with a straight road width of 9 m and a bend road width of 18 m. The form of drainage that is made is a channel with a trapezoid shape and a settling pond. The mining method used is open pit with down-dip excavation. Mining sequences and production schedules are divided into 4 mining sequences to obtain a production target of ±16,000 tons/month.